REPORT ON THE AVAILABILITY OF QUANTUM AND GLIDE SOFTWARE ON DOCKING LIGANDS-PROTEIN - Mi, Nguyen Hoa; Van, Dang Ung; Long, Le Kim; Thiem, Lam Ngoc; Huy, Do Quang (Vietnam Journal of Chemistry, 2012)
A series of the complexes of human CD38’s wild type, E226 and E146 mutants as well have been simulated. The biosoftwares well simulate the penetration of nicotinamide-adenine-dinucleotide (NAD) into the active site. The breaking down hydrogen bond between 2’-3’ OH ribosyl and the residues replaced Glu226 makes NAD to be less constrained in active site and nicotinamide (NA) becomes more difficult to be cleaved and eliminates the mutant catalytic activities. The large majority of the substrate NAD is hydrolyzed to ADPR while the conversion of NAD to cADPR is not the dominant reaction catalyzed by wild-type human CD38. These results are in good agreement with the previous crystallographic analysis and the experiments quantified the catalytic activities of human CD38 and its mutants.